Faktor yang Berhubungan dengan Kepatuhan Penggunaan Alat Pelindung Diri pada Pekerja Bengkel Las di Kecamatan Kota Soe - Ansi Imani Nino; Jacob Matheos Ratu; Marylin Susanti Junias (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Welding workshops operating in Soe City District on average employ around 4-6 people with a minimum education of elementary school-graduate level. The welding process using electric power exposes workers directly to the dangers in the workplace. It is necessary to have Personal Protective Equipment (PPE) worn by workers while working and while in the workplace environment. The aim of this research is to determine factors related to compliance with the use of Personal Protective Equipment (PPE) among welding workshop workers in Soe City District. Sampling in this study used simple random sampling with a sample size of 94 people. Analysis of this relationship uses the chi square test as an alternative test. The research results show that there is a relationship between knowledge (p value=0.004), attitude (p value=0.001), availability of personal protective equipment (p value=0.008), and there is no relationship between education (p= value= 0.642), age (p value=0.294), and work accidents (p value=0.483) with compliance with the use of Personal Protective Equipment (PPE) among welding workshop workers in Soe City District.